International debt crises: new instruments designed to restructure sovereign bond issues - Kathrin Berensmann (Deutsches Institut für Entwicklungspolitik (DIE), 2003)
The frequency with which international financial crises have occurred since the mid-1990s (Asia 1997, Russia 1998, Brazil 1999, and Argentina 2001) points to the need to reform the international financial architecture. The emergence of and the unregulated approaches used to resolve financial crises lead to major welfare losses in the countries affected and constitute a risk to the stability of the international financial system.Instruments tailored to restructuring sovereign foreign debt therefore constitute an essential element of the international financial architecture. However, these mechanisms have not been developed in keeping with the farreaching upheavals which globalization have entailed for the international financial markets.One important feature of the expansion of globalization in the 1990s was a huge rise in and an altered structure of international capital flows. Sovereign bond issues held by heterogeneous groups of creditors assumed an entirely new significance in the 1990s compared to bank credits, which dominated in the 1970s and 1980s.In the case that a sovereign state is forced to default on a bond issue, the heterogeneous makeup of the creditor structure gives rise to serious problems involving coordination and collective action that cannot be resolved without recourse to new instruments. Under current circumstances a restructuring of bonds takes several years, as can be clearly seen in the case of Argentina.In view of the fact that at present most actors in the international financial markets reject an international insolvency procedure, both a voluntary code of conduct and collective action clauses constitute, in the short term, the most important instruments for restructuring sovereign bond issues. In the medium term, though, an insolvency procedure can play an important role here, since a procedure of this kind is a comprehensive instrument well suited to coordinating different creditor groups prior to and during a debt crisis.
Keywords: 330